PENERAPAN DE MINIMIS VALUE DALAM PROSES PENETAPAN NILAI PABEAN BARANG KIRIMAN IMPOR PADA KPPBC TMP B PEKANBARU - Dafa Gusfananda Suharto (Jurnal Acitya Ardana, 2021)
This qualitative method of research aims to determine the impact of de minimis value policy related to the enactment of Regulation of the Minister of Finance (PMK) No. 199/PMK.010/2019 in the process of determining the customs value of imported shipments at the Office of Supervision and Service of Customs and Excise Type B Pekanbaru Customs. Instruments in this study in the form of reviews in the field and interviews to the officer of the section inspector of Customs and Excise Services VI KPPBC TMP B Pekanbaru which directly handles the business process of imported shipments. From the results of the study can be concluded that the policy de minimis value of imported shipments has a significant effect on the process of determining the customs value of goods delivered at KPPBC TMP B Pekanbaru. Related to the problem found from the business process of determining the customs value of imported shipments is difficulty when making determinations in accordance with the provisions of the customs value, this is due to the commodity goods that are determined difficult to find information on customs value. Another problem found is the unused database of customs value as an instrument of fairness test the customs value of the goods concerned as well as the treatment of vouchers and discounts that still confuse the public.